Tyrosine kinase inhibitor and rituximab‐CHOP treatment for concurrent chronic myeloid leukemia and non‐Hodgkin lymphoma: a case report. Issue 12 (2nd November 2017) - Takeyasu, Yuki; Satake, Atsushi; Azuma, Yoshiko; Tsubokura, Yukie; Yoshimura, Hideaki; Hotta, Masaaki; Nakanishi, Takahisa; Fujita, Shinya; Nakaya, Aya; Ito, Tomoki; Nomura, Shosaku
Key Clinical Message: Non‐Hodgkin lymphoma can occur concurrently with chronic phase‐chronic myeloid leukemia (CML) at initial diagnosis. Combination treatment with second‐generation tyrosine kinase inhibitors and rituximab‐CHOP for patients newly diagnosed with CML and non‐Hodgkin lymphoma is effective for both diseases. However, we found that this treatment combination may induce severe myelosuppression. Abstract : Non‐Hodgkin lymphoma can occur concurrently with chronic‐phase chronic myeloid leukemia (CML) at initial diagnosis. Combination treatment with second‐generation tyrosine kinase inhibitors and rituximab‐CHOP for patients newly diagnosed with CML and non‐Hodgkin lymphoma is effective for both diseases. However, we found that this treatment combination may induce severe myelosuppression.